Aliens versus Tea-Party Patriots: Falling Skies and the Post-Apocalyptic Survival Narrative in the Age of Obama. - Hantke, Steffen (Journal of Language, Literature & Culture, 2014)
In an alignment of recent right-wing populism-especially that of the so-called Tea Party-with post-invasion narratives, the television series Falling Skies recasts conservative populist visions of anti-government activism in the popular vernacular of science fiction. By mobilizing and exploring the iconography of the Revolutionary War in the service of defining national identity and legitimizing the need for an armed citizenry, the series responds to a distinct phase in the political activism of the Tea Party during the Obama presidency, defined by the economic crisis of 2008 and its aftermath.